Pengaruh Social Media Marketing Instagram, Brand Awareness Terhadap Keputusan Pembelian: (Studi Konsumen Nhunu Shop Sorong) - Sofia, Susetyowati; Wally, Sarmila; Wijiastuti, Retno Dewi; Rahayu, Agilistya (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
The Influence of Instagram Social Media Marketing, Brand Awareness on Purchasing Decisions (Nhunu Shop Sorong Consumer Study). This study has the following formulation: 1). Does Instagram Social Media Marketing have a significant influence on purchasing decisions at Nhunu Shop in Sorong City?; 2). Does Brand Awareness have a significant influence on purchasing decisions at Nhunu Shop in Sorong City?; 3). Do Instagram Social Media Marketing and Brand Awareness simultaneously have a significant influence on purchasing decisions at Nhunu Shop in Sorong City?. This study aims to determine the influence of Instagram social media marketing (X1) and brand awareness (X2) on purchasing decisions (Y) of Nhunu Shop consumers in Sorong City. This study uses a quantitative approach with a descriptive method with a population of 749. Sampling uses a non-probability sampling method with a purposive sampling technique and sample criteria focused on consumers who shop more than once as many as 374 so that the number of samples in this study is 193 samples. The results of this research analysis indicate that the Instagram social media marketing variable (X1) has a positive and significant effect on the purchasing decision variable (Y), the brand awareness variable (X2) has a positive and significant effect on the purchasing decision variable (Y). The Instagram social media marketing and brand awareness variables simultaneously have a positive and significant effect on purchasing decisions (Y).